Pounding performance between a seismic-isolated long-span girder bridge and its approaches. (1st July 2022) - Guo, Wei; Li, Jianzhong; Guan, Zhongguo; Chen, Xu
Highlights: Investigate pounding performance of long-span girder bridges under earthquakes. Seismic isolation bearings can reduce the probability of pounding by tuning responses of adjacent units. Pounding is more likely to happen when considering near-fault motions and wave passage effect. Abstract: For girder bridges located in regions with a high seismic hazard level, seismic isolation bearings are usually implemented to suppress the seismic inertial force transmitted from the superstructure to substructures, protecting the pier columns and foundations. However, whether potential pounding might happen for these seismic-isolated girder bridges between adjacent units are scarcely considered, especially for those with long spans where the wave passage effect is of great significance. This paper develops a finite element model for a typical hybrid truss-girder bridge, based on which the influence of seismic isolation bearings and wave passage effect on pounding is carefully investigated considering both near-fault and far-field motions. The results show that for this type of long-span girder bridges, pounding may happen even the adjacent bridge units are designed with similar vibration periods, especially when near-fault motions and wave passage effect are considered. Under non-uniform excitations with different apparent wave velocities, the employment of isolation bearings can reduce the relative displacement at expansion joints and thus improve the performance against pounding; however, the occurrence of pounding and damage of expansion joints cannot be fully avoided. Further, motions with lower apparent velocities generally correspond to more devastating responses, which should be particularly considered during engineering practice.